Formação de professores para relações étnico-raciais no contexto de uma escola com estudantes bolivianos - Santos, Elisângela Nogueira Janoni dos (2018)
With the objective of analyzing the resonance of a continuous training course of teachers in a public school in the city of São Paulo in relation to teaching practice and interpersonal relations in the perspective of Education for ethnic-racial relations, the research focused on the presence of Bolivian students in this school and sought to understand the migratory phenomenon Bolivia-Brazil and its consequences in the inclusion of them. The importance of approaching the theme is justified by the diversity of ethnicities and cultures present in our country. In this school unit, there was a need to increase the knowledge of the different Latin cultures, due to the great immigration (mainly Bolivian) and the insertion of these immigrants and / or their descendants into the school community. To do so, the data collection procedures of this qualitative research were questionnaires with teachers involved in the training developed in 2015 or in project practices with immigrant students in the school unit and questionnaires applied to Bolivian immigrant students or descendants of the seventh, eighth and ninety years. The questions that surrounded the problematic of this research were: "What are the resonances of this formation about ethnic-racial relations in the teaching practice? Have there been changes? In what aspects? " Thus, the objective was to analyze the effects of this training on ethnic-racial relations between the different members of the school community in the period from 2015 to 2018, as well as the view of the students involved and the establishment of their ethnic-racial relations. Understanding these phenomena through the view of teachers and students is an exercise of listening in the dialogical and horizontal perspective of the relations founded in Paulo Freire. The results of the research point to resonances from teacher education, promoting projects related to diversity and interculturality, as well as increasing the participation of immigrant students in these projects, improving communication and school climate